Retardo de crecimiento intrauterino en los recién nacidos de la Unidad de Neonatología del Hospital General Isidro Ayora periodo enero - junio 2016. - Jaramillo Mendoza, Hover Daniel (2017)
Intrauterine growth retardation (IUGR) is considered for any newborn that is below the 10th percentile in relation to their gestational age, it remains a public health problem in Ecuador. The present study was a descriptive, prospective, qualitative and quantitative cross-sectional study conducted at the Neonatology Unit of the Hospital Isidro Ayora. The general objective was to observe the intrauterine growth retardation of the Newborns of the Neonatology Unit of the General Hospital Isidro Ayora de Loja. During the study period, 46 newborns with intrauterine growth retardation were admitted, where the most common maternal pathology was Vaginosis with 50%. Among the complications presented by Newborns we found hyperbilirubinemia in 47.8%, in terms of classification of growth retardation there was a predominance of asymmetric intrauterine growth retardation with 71.7%, male gender was the most affected 56.5%, and finally in relation to gestational age it was found that 82.6% of term newborns presented IUGR. Keywords: Newborn, Maternal Pathology, Delayed Intrauterine Growth.